An overview of the principle of complementarity in international criminal law (2016)
The Rome Statute of the International Criminal Court (ICC Statute)1 established the International Criminal Court (ICC) with jurisdiction over international core crimes outlined in Article 5(1) of the Statute. 2 In the same vein, states within the international community have the duty to prosecute these core crimes under international customary law.1 In effect, the jurisdiction of national courts runs concurrently with the jurisdiction of the ICC over these core crimes. This raises the issue of precedence of jurisdiction identified with the operation of previous ad hoc international criminal tribunals4 * which had primacy in the exercise of jurisdiction over national courts of states where they operated. The jurisdiction of the ICC is however founded on the principle of complementarity which gives primacy to national courts over the ICC. The principle of complementarity, though not necessarily a new concept, is expounded by the provisions of the ICC Statute. This article is an overview of the principle of complementarity as articulated in the ICC Statute. It examines the provision of Article 17 of the ICC Statute in relation to the jurisdiction of the ICC over international core crimes and the duty of state parties to prosecute these crimes. It concludes on the premise that the principle of complementarity has a few practical issues relating to its application and examines briefly the ongoing preliminary examination of the Nigerian situation by the ICC.